2011
DOI: 10.1177/1359104510366284
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners’ attitudes towards the use of standardized diagnostic assessment in routine practice: A qualitative study in two Child and Adolescent Mental Health Services

Abstract: There is tension within Child and Adolescent Mental Health Services (CAMHS) assessments between the richness of differing practitioner's perspectives and maintaining a basic level of assessment that is acceptable to all disciplines. Standardized assessments are mandatory in research, yet are rarely applied systematically across CAMHS.The use of standardized assessments in routine practice might aid the allocation of families to the practitioners best able to meet their needs and free up time for intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 18 publications
3
65
0
6
Order By: Relevance
“…For example, we found that clinicians who were top implementers (based on rates of measure completion and feedback viewing) believed that the MFS empowered clients and enhanced the client-clinician relationship through the process of engaging clients in reporting on outcomes and facilitating clinical conversation based on feedback. These anecdotal findings are consistent with the personcentered themes from qualitative studies of routine outcome monitoring (Hall et al 2014;Martin et al 2011;Unsworth et al 2012;Wolpert et al 2014).…”
Section: Integration With Clinical Values and Workflowsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, we found that clinicians who were top implementers (based on rates of measure completion and feedback viewing) believed that the MFS empowered clients and enhanced the client-clinician relationship through the process of engaging clients in reporting on outcomes and facilitating clinical conversation based on feedback. These anecdotal findings are consistent with the personcentered themes from qualitative studies of routine outcome monitoring (Hall et al 2014;Martin et al 2011;Unsworth et al 2012;Wolpert et al 2014).…”
Section: Integration With Clinical Values and Workflowsupporting
confidence: 86%
“…There are practical (e.g., time burden, organizational and managerial resources) and philosophical barriers (e.g., clinician perceptions and attitudes) (Boswell et al 2013;Duncan and Murray 2012). The regular use of data from feedback in clinical decision-making may seem antithetical to the person-centered values of a typical clinician (Fitzpatrick 2012;Martin et al 2011;Wolpert et al 2014). Sustainable implementation requires intensive support for individual attitude and knowledge shifts Hall et al 2014;Unsworth et al 2012) and organizational culture change using complex and subtle implementation methodologies and post-implementation strategies (Mellor-Clark et al 2014).…”
Section: Integration With Clinical Values and Workflowmentioning
confidence: 97%
“…In general, HCPs were supportive of using outcome measures as an adjunct to support clinical opinion, but some raised concerns about favouring outcome measures over clinical judgment [4,15]. …”
Section: Resultsmentioning
confidence: 99%
“…It is encouraging for such systems as CYP-IAPT to observe that families do not perceive it as a burden which may help HCPs overcome some concerns with asking patients to complete multiple forms [15]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation